Fundamentals of electrical power engineering - Al-Arainy, Abdulrhman Ali; Malik, Nazar Hussain; Al-Ghuwainem, Saad Mubarak (Riyadh : King Saud university, academic publishing and press, 2007)
Traditionally, electric power engineering related courses form a main component of any electrical engineering curriculum. However, with the rapid growth in other fields such as electronics, communication, computers and control system, undergraduate electrical engineering students have to be exposed to a multitude of courses in these areas as well. As a result, time available for teaching traditional courses has decreased significantly. Therefore, there was a need to condense the basic essential material into a single, self-contained textbook for one-semester course dealing with the core concepts of electrical power engineering
1. Introduction -- 2. Power system components and layout -- 3. Electric power generation -- 4. Transmission line parameters -- 5. Transmission line modeling and operation -- 6. Power cables -- 7. Overhead line insulators -- 8.Power system representation -- 9. Per unit system of calculations -- 10. Distribution systems -- 11. Grounding in power system --12. Overvoltage and overcurrent protection in power system -- index.
Includes bibliographical references and index
Keywords: Electrical engineering; Electrical power